2023
DOI: 10.1186/s12902-023-01370-x
|View full text |Cite
|
Sign up to set email alerts
|

Left parathyroid carcinoma with secondary hyperparathyroidism: a case report

Abstract: Background Parathyroid carcinoma is a rare disease with a frequency of 0.005% of all malignancies [1, 2]. Various aspects of its pathogenesis, diagnosis, and treatment remain poorly understood. Furthermore, cases with secondary hyperparathyroidism are fewer. In this case report, we describe a case of left parathyroid carcinoma with secondary hyperparathyroidism. Case presentation The patient was a 54-year-old woman who had been on hemodialysis sinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Of all ESRD patients undergoing PTx, nodular hyperplasia is the most common histopathological result reported in the literature, followed by diffuse hyperplasia, while malignancy is found only in an anecdotic number of cases [ 14 , 57 ]. Preoperative higher MIBI uptake is, generally, associated with a considerably higher prevalence of nodular hyperplasia, higher gland weight, and greater cell proliferation [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of all ESRD patients undergoing PTx, nodular hyperplasia is the most common histopathological result reported in the literature, followed by diffuse hyperplasia, while malignancy is found only in an anecdotic number of cases [ 14 , 57 ]. Preoperative higher MIBI uptake is, generally, associated with a considerably higher prevalence of nodular hyperplasia, higher gland weight, and greater cell proliferation [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative higher MIBI uptake is, generally, associated with a considerably higher prevalence of nodular hyperplasia, higher gland weight, and greater cell proliferation [ 57 , 58 ]. Yokoyama et al [ 14 ] identified 37 PC cases in SHPT reported until 2022. Up to the writing of this manuscript, five more cases have been published ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased incidence of parathyroid carcinoma has been associated with ESRD [ 19 ]. According to the literature, the mean age is 55 years, with approximately equal sex distribution [ 9 ]. The biochemical and clinical characteristics are characterized by markedly elevated serum calcium, PHT and target-organ damage [ 20 ].…”
Section: Discussionmentioning
confidence: 99%